An innovative model of human resource administration inthe civil serviceof Ukraine - Goncharuk, Natalia; Pyrohova, Yuliia (My University, 2020)
The article is devoted to the research of the modern systemof personnelmanagement in state and local self-government bodies and creation of an innovativemodelofhuman resources management in the public service in Ukraine. It has been establishedthat themodernization of personnel services into personnel management services startedinthepublicauthorities after the approval of the Strategy of the state personnel policy for 2012-2020, theStrategy of reforming the public administration of Ukraine for the period up to 2021andtheadoption of the new Law of Ukraine "On Civil Service" and continues today. Analysisoftheexisting personnel management system in state bodies and bodies of local self-government, itsstrengths and weaknesses has identified a number of systemic problems, and also, that todayinUkraine there is no single, legally regulated system of personnel management inthepublicservice in general and of the personnel management system in the sphere of state serviceandservice in bodies of local self-government in particular. A large number of legal documentsgoverns this system and only fragmentary reflected in them. It is proposed, tosolvetheseproblems and improve the management of human resources in the public service inUkraine, tomove from personnel management to a qualitatively new level of service strategic managementof human resources. It have been defined the main purpose, objectives and functionsoftheoffice of strategic human resource management in the public service, and have beendevelopeda model of strategic human resource management in the public service and mechanismsforitsimplementation.
Keywords: управління персоналом; органи державної влади; місцеве самоврядування; інноваційна модель управління персоналом; державна служба; державне управління; Стратегія державної кадрової політики; Стратегія реформування державного управління України